2021
DOI: 10.3389/fmicb.2021.757914
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of a Novel Anti-tuberculosis Compound That Targets Deoxyuridine 5′-Triphosphate Nucleotidohydrolase

Abstract: Tuberculosis (TB) is still a threat to humans worldwide. The rise of drug-resistant TB strains has escalated the need for developing effective anti-TB agents. Deoxyuridine 5′-triphosphate nucleotidohydrolase (dUTPase) is essential for thymidylate biosynthesis to maintain the DNA integrity. In Mycobacterium tuberculosis, dUTPase provides the sole source for thymidylate biosynthesis, which also has the specific five-residue loop and the binding pockets absent in human dUTPase. Therefore, dUTPase has been regarde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…SAR studies have not performed by them. [36] Moreover, compound 4 has been found with the IC 50 of 0.80 � 0.09 μM against mycobacterial deoxyuridine triphosphate nucleotidohydrolase (dUTPase), inhibiting the thymidylate biosynthesis in mycobacteria. The molecular docking revealed to inhibit mycobacterial deoxyuridine-5triphosphate nucleotidohydrolase (dUTPase, PDB ID: 1SIX) by binding to its P79 catalytic residue among the five-residue loop, which has been absent within human dUTPase.…”
Section: Benzimidazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…SAR studies have not performed by them. [36] Moreover, compound 4 has been found with the IC 50 of 0.80 � 0.09 μM against mycobacterial deoxyuridine triphosphate nucleotidohydrolase (dUTPase), inhibiting the thymidylate biosynthesis in mycobacteria. The molecular docking revealed to inhibit mycobacterial deoxyuridine-5triphosphate nucleotidohydrolase (dUTPase, PDB ID: 1SIX) by binding to its P79 catalytic residue among the five-residue loop, which has been absent within human dUTPase.…”
Section: Benzimidazolesmentioning
confidence: 99%
“…The compound 34 have been found to act on the protein encoded by rpoB gene as revealed through in silico molecular dynamics study and mutation study. [62] Jeyachandran et al have reported 2-(aryloxy methyl)aziridines ( 35) and 2-((3-aryl-1phenylallyloxy)methyl)aziridine (36) with MIC of 0.5 μg/mL having three-fold activity than standard drugs like ciprofloxacin and ethambutol as compared to ethambutol (MIC of 0.5 μg/ mL). [63] Chakravarty et al have reported anthracenyl phosphonate and π-conjugated acid cocrystals (37) with MIC of 1.56 μg/ mL, as active as ethambutol.…”
Section: Othersmentioning
confidence: 99%